Mystery rhymes - Rushton, Sharon; Fairbridge, John (Macmillan Education Australia South Yarra, Vic., 1997)
Mystery Rhymes by Sharon Rushton is a captivating children's book that combines poetry and mystery to engage young readers. Each rhyme presents a whimsical mystery, inviting children to solve puzzles and uncover clues hidden within the playful verses. The book encourages creativity and critical thinking as readers are challenged to think outside the box while enjoying the rhythm and flow of the poems. With delightful illustrations accompanying the engaging rhymes, this collection fosters a love for language and storytelling, making it an enjoyable and interactive experience for children as they embark on their journey of discovery and imagination.